FLUX AND REJECTION OF SALTS BY USING COMMERCIAL NANOFILTRATION MEMBRANES - ALFATESH, MOHAMMED TAHER (IRC, 2016)
The deficiency of fresh water has become a major issue and globally the demand has been enlarged. Accordingly, there is a need to further investment and studies to overcome this problem. For instance, nanofiltration membrane processes are used in several applications particularly in water purification and desalination. Thus, in this project, three different types of nanofiltration membranes (Microdyn Nadir NT102, NT103 and NP030) were used to study the flux and rejection of salts NaCl, MgCl2. These membranes have been characterized by using Scanning electron microscopy (SEM) with the aim of morphology and cross section.